Anion‐π Catalysis: Focus on Nonadjacent Stereocenters. Issue 2 (8th February 2018) - Zhang, Xiang; Liu, Le; López‐Andarias, Javier; Wang, Chao; Sakai, Naomi; Matile, Stefan
Abstract : Anion‐ π interactions have been recently introduced to catalysis with the idea to stabilize anionic intermediates on π ‐acidic surfaces. Realized examples include enolate, enamine and iminium chemistry, domino processes and Diels–Alder reactions. Moving on from the formation of contiguous stereogenic centers on π ‐acidic surfaces, herein we report the first asymmetric anion‐ π catalysis of cascade reactions that afford nonadjacent stereocenters. Conjugate addition‐protonation of achiral disubstituted enolate donors to 2‐chloroacrylonitrile generates 1, 3‐nonadjacent stereocenters with moderate enantioselectivity and diastereoselectivity. The explored catalysts operate with complementary naphthalenediimide and fullerene surfaces with highly positive quadrupole moments and high polarizability, respectively, and proximal amine bases. We find that anion‐ π catalysts can increase the diastereoselectivity of the reaction beyond the maximal 1:4.0 dr with conventional catalysts to maximal 5.3:1 dr on the large fullerene surfaces. The enantioselectivity of anion‐ π catalysts, best on the confined naphthalenediimide surfaces with strong quadrupole moment, exceed the performance of conventional catalysts except for comparable results with a new, most compact, surprisingly powerful bifunctional control catalyst. Simultaneously increased rates and stereoselectivities compared to control catalysts without π ‐acidic surface support that contributions of anion‐ π interactions to the catalytic cascade process are significant. Abstract :